1311 Outcomes for facilitators through workplace environmental improvement using a participatory approach. (24th April 2018) - Yoshikawa, E; Yoshikawa, T; Kogi, K
Abstract : Introduction: The purpose of this study was to determine changes in awareness, behaviour, and relationships of facilitators who were involved in participatory workplace environment improvement and to examine the outcome components that led to meaningful workplace organisation resulting in workplace environmental improvements through a participatory approach. It is useful to clarify these outcome components in relationship to associations among various factors. Methods: An anonymous self-administered questionnaire survey was conducted for 91 facilitators in three organisations. Valid responses from 79 facilitators (91.9%) were analysed. Changes in awareness, behaviour and relationships as a result of participatory workplace environment improvement were studied. A conceptual framework of the outcome of changes in the overall workplace organisation was set as a tentative model. Exploratory factor analysis was used to determine outcome elements for the facilitators in the participatory process by means of hierarchal regression analysis. This study was approved by the ethics review committee of St. Luke's International University (13–042). Results: Outcomes for facilitators consisted of four sub-concepts corresponding to 'developing self-confidence, ' 'improving work-related risk sensitivity, ' 'gaining better-than-expected results based on establishing relationships with workers' and 'knowing practical ways and strategies to ensure full participation.' The range of Cronbach's alpha of the subscales was 0.82–0.95. The results of hierarchal regression analysis indicated that sub-concepts of 'knowing practical ways and strategies to ensure full participation' were significantly associated with age (B=−0.261, p=0.042), and that 'developing self-confidence' was significantly associated with active participation (B=0.348, p=0.006) and number of improvements (B=0.251, p=0.042). Conclusion: The outcomes revealed confirmed the importance of applying practical ways to secure active participation of workers/managers at the workplace level. These outcomes were associated with satisfaction of improvements based on experiences of these improvements. Supporting satisfaction of improvements in the follow-up activities was considered useful for effective workplace environment improvement.